Effectiveness of Teaching Assistance Implementation at SMA Kristen Rantepao as an Embodiment of the Independent Learning - Independent Campus (MBKM) Program - Sam Hermansyah; Nur Hikmah; M.Halil Gibran; Nur Rahma; Isumarni Isumarni; Nurul Faradillah; Aditia Guntur; Aliffia Putri Saharani (Universitas Muhammadiyah Enrekang, 2024)
This study evaluates the implementation of teaching assistance as an embodiment of the Independent Learning - Independent Campus (MBKM) program, focusing on its effectiveness for both educators and students at the high school level. Conducted at SMA Kristen Rantepao, the research employs a quantitative approach, utilizing digital questionnaires via Google Forms to gather data. The findings center on three key aspects of student activities: (a) interaction and socialization levels, (b) collaboration with teachers, and (c) emotional connections with students to boost motivation and learning enthusiasm. The results demonstrate a significant positive impact, with educators acknowledging the program's role in easing their teaching burdens and inspiring students with innovative and creative teaching methods. This program has been identified as effective in enhancing student learning engagement and fostering collaboration among all stakeholders. To optimize the outcomes, it is recommended to provide comprehensive training for participating students.